Current approaches to the analysis of design extension conditions with core melting for new nuclear power plants (International Atomic Energy Agency, 2021)
"The focus of this publication is on collecting current practices in Member States related to design extension conditions (DECs) with core melting. The information provided is based on the feedback from technical experts from Canada, France, Finland, India, the Islamic Republic of Iran, the Russian Federation, and the United States of America. There is, however, still no common understanding of DECs due to the complexity of phenomena and insufficient experimental data. This publication identifies current approaches of IAEA Member States with active nuclear power programmes and discusses the regulatory perspective and technical rationale. It attempts to find common practices and possible areas for harmonization of the main rules related to the analysis of DECs with core melting for new water cooled reactors, including their selection for the safety demonstration."--Publisher's website.
"October 2021"--Title page verso.
Keywords: Nuclear power plants -- Design and construction.; Nuclear power plants -- Safety measures.; Nuclear reactors -- Cores.; elektronické knihy; electronic books